Pengembangan Sistem Aplikasi Manajemen Distribusi Pupuk Berbasis Web (Studi Kasus: PT Petrokimia Gresik) - Moh. Wahyu Dwi Ridiansyah; Fajar Pradana; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Petrokimia Gresik is a state-owned enterprise that produces subsidized and non-subsidized fertilizers. In the distribution activities, there were several problems found. The first problem felt by a staff of the Department of Regional 1 was having problems in processing reporting data from the buffer warehouse because of the large amount of data available. The second problem was felt by the Regional 1 Manager who complained of the difficulty of monitoring the condition of the stock in the area quickly and efficiently. The third problem was complained by the Department of Regional 1 staff regarding the reporting of damaged fertilizer in Warehouse Buffer, the process that occurs now is inefficient and there are no media that can monitor the delivery of damaged fertilizer to the central warehouse for recycling. The fourth problem complained by the staff in the inventory section complained that the process was not efficient because the results of the stock inventory must be manually adjusted to the stock listing. Based on these problems, the system developer will do this research that can solve the problem. The waterfall method is used in the software development process in this study. The stages carried out in this study are literature study, needs analysis, system design and implementation, testing, taking conclusions and suggestions. The development of this system is web-based using the CodeIgniter framework. To create a map of the condition of the regional stock used the Google Maps API is equipped with KML layering. Unit and integration testing is done using the white box testing method with 100% valid results. Validation testing uses the black box testing method with 100% valid results. Compatibility testing is done with three different browsers with 100% valid results.